Trust motivation: The self-regulatory processes underlying trust decisions. (May 2019) - van der Werff, Lisa; Legood, Alison; Buckley, Finian; Weibel, Antoinette; de Cremer, David
Theorizing about trust has focused predominantly on cognitive trust cues such as trustworthiness, portraying the trustor as a relatively passive observer reacting to the attributes of the other party. Using self-determination and control theories of motivation, we propose a model of trust motivation that explores the intraindividual processes involved in the volitional aspects of trust decision-making implied by the definition of trust as a willingness to be vulnerable. We distinguish between intrinsic and extrinsic drivers of trust and propose a two-phase model of trust goal setting and trust regulation. Our model offers a dynamic view of the trusting process and a framework for understanding how trust cognition, affect and behavior interact over time. Furthermore, we discuss how trust goals may be altered or abandoned via a feedback loop during the trust regulation process. We conclude with a discussion of potential implications for existing theory and future research.